2010
DOI: 10.2215/cjn.01510210
|View full text |Cite
|
Sign up to set email alerts
|

The State of U.S. Living Kidney Donors

Abstract: Conclusions: Almost one quarter of living donors have medical conditions that may be associated with future health risk. Close follow-up and a registry of these donors are necessary. Only then will we be able to inform prospective living donors most accurately of the real risk of donation on their health and survival. Additionally, these data speak to the need for a national discussion on the provision of health insurance for living donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 56 publications
(37 reference statements)
2
68
1
Order By: Relevance
“…Potential financial considerations for LKDs (with limited empirical evidence) include any effect on life and health insurability (21). In addition, it is known that almost one fifth of current LKDs lack health insurance (22). At-risk donors are more likely to be black, have lower educational attainment, or not be a United States citizen (22).…”
Section: Background On Systemic Barriers To Living Kidney Donationmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential financial considerations for LKDs (with limited empirical evidence) include any effect on life and health insurability (21). In addition, it is known that almost one fifth of current LKDs lack health insurance (22). At-risk donors are more likely to be black, have lower educational attainment, or not be a United States citizen (22).…”
Section: Background On Systemic Barriers To Living Kidney Donationmentioning
confidence: 99%
“…In addition, it is known that almost one fifth of current LKDs lack health insurance (22). At-risk donors are more likely to be black, have lower educational attainment, or not be a United States citizen (22). For these donors, out-of-pocket expenditures associated with medical care may be more extensive in the long term.…”
Section: Background On Systemic Barriers To Living Kidney Donationmentioning
confidence: 99%
“…14 Hypertension is present in 30% of the general population, and the prevalence increases with age; some studies report that it is present in 2% of living donors at the time of donation (we observed a rate of 5%) and develops in up to 40% of donors over time. 15,16 Garg and associates reported a 10-year hypertension rate of 16% postdonation, about 5% higher than in the control population. 16 The literature suggests that transplant programs generally exclude donors with a BMI > 35 kg/m², and 10% of programs exclude donors with a BMI > 30 kg/m².…”
Section: Discussionmentioning
confidence: 96%
“…15,16 Garg and associates reported a 10-year hypertension rate of 16% postdonation, about 5% higher than in the control population. 16 The literature suggests that transplant programs generally exclude donors with a BMI > 35 kg/m², and 10% of programs exclude donors with a BMI > 30 kg/m². 17 Hassan and associates found that a higher BMI is the single predonation variable associated with every adverse postdonation outcome except for death, and each increase of 1 kg/m² is associated with a 3% to 10% higher risk of proteinuria and a reduced glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 96%
“…The spectrum of health in accepted donors with isolated medical abnormalities has ranged from subtle metabolic abnormalities to early pre-clinical disease states that may portend future risk [2]. In fact, contemporary donors are older, heavier, and carry more risk factors for chronic kidney disease than donors in earlier generations [3][4][5]. Additionally, recent data suggesting that live kidney donors have higher rates of end-stage renal disease in the long-term compared with otherwise similar healthy persons [6••, 7] highlights the importance of careful predonation selection, including assessment of renal function and structure as critical components of the donor evaluation.…”
Section: Introductionmentioning
confidence: 99%